2022
DOI: 10.1227/ons.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Tissue Plasminogen Activator Infusion Using a Minimally Invasive Irrigating Catheter for the Treatment of Intraparenchymal Hemorrhage Within the Basal Ganglia: Case Reports

Abstract: BACKGROUND AND IMPORTANCE: Intraparenchymal hemorrhage (IPH) is a debilitating and highly morbid type of stroke with limited effective treatment modalities. Minimally invasive evacuation with tissue plasminogen activator (rt-PA) has demonstrated promise for mortality/functional improvements with adequate clot volume reduction. In this study, we report 2 cases of continuous rt-PA infusion using a closed circuit, dual lumen catheter, and irrigation system (IRRAflow) for IPH treatment. CLINICAL PRESENTATION: A 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Routine CT and MRI examinations can be performed to detect occupancy at the site of the lesion. The clinical symptoms and imaging results of occupancy effects may not show any signs of a cerebral hemorrhage, such as loss of consciousness, hemiparesis, and severe headaches in patients [7,8,17], thus increasing the chances of misdiagnosing the disease as a brain tumor. Our patient had an acute onset and a short duration of illness, which indicated a clinical manifestation that was different from a tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine CT and MRI examinations can be performed to detect occupancy at the site of the lesion. The clinical symptoms and imaging results of occupancy effects may not show any signs of a cerebral hemorrhage, such as loss of consciousness, hemiparesis, and severe headaches in patients [7,8,17], thus increasing the chances of misdiagnosing the disease as a brain tumor. Our patient had an acute onset and a short duration of illness, which indicated a clinical manifestation that was different from a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…There were prominent vascular markings anterior and posterior to the brain stem on MRI (high signal with contrast and voids on T2 images), which pointed to the possibility of AVF. We ruled out the possibility of an intracranial hemorrhagic lesion, which is often associated with increased intracranial pressure, severe headache, or loss of consciousness [6][7][8]. To further clarify the diagnosis, we performed a digital subtraction angiography We ruled out the possibility of an intracranial hemorrhagic lesion, which is often associated with increased intracranial pressure, severe headache, or loss of consciousness [6][7][8].…”
Section: Case Presentationmentioning
confidence: 99%
“…Previous studies have reported excellent results with the IR-RAflow in a variety of conditions. [3][4][5][6][7] No reports have yet been published that guide the technical utilization of the IRRAflow, including delivering IT medications.…”
mentioning
confidence: 99%